The Polycladida (Platyhelminthes) of the Canary Islands. New genus, species and records - Cuadrado, Daniel; Moro, Leopoldo; Noreña, Carolina (Zootaxa, 2017)
The main focus of this study is the biodiversity of the order Polycladida in the Canary Islands, archipelago belonging to Macaronesia and to the Mediterranean basin hot spot region. Polycladida is a cosmopolitan order with some species distributed worldwide; but it also is comprised of endemic species. Here, 19 polyclad species are revised and determined, ten of which were previously recorded for the Canary Islands (De Vera et al. 2009). A new genus and species Multisepta fengari n. gen., n. sp., of the suborder Acotylea and five new species belonging to the suborder Cotylea including Anonymus ruber n. sp., Enchiridium magec n. sp., Eurylepta guayota n. sp., Acanthozoon aranfaibo n. sp. and Pseudoceros mororum n. sp., are presented and described. In addition, two well-known species, Pseudobiceros wirtzi (Madeira and Cape Verde) and Pericelis cata (Caribbean coasts), are new records for the Canary Islands and for the hot spot region of the Mediterranean basin. Using all available information, including from the morphological study presented here, a key for the species for the Canary Islands has been generated.